Unusual Combination of Multiple Vascular Anomalies in a German Shepherd Puppy with Megaoesophagus. (3rd January 2017) - Biasato, I.; Lanteri, G.; Guarda, F.; Capucchio, M. T.; Marino, F.; Briguglio, G.; Macrì, F.
Summary: A 2‐months‐old male German shepherd puppy was referred for regurgitation and delayed growth. Radiographic and endoscopic investigations revealed a precardiac megaoesophagus and oesophageal constriction at the level of the heart base. At post‐mortem examination, a specific form of persistent right aortic arch characterized by an aberrant left subclavian artery in combination with a ligamentum arteriosum originating at the aberrant left subclavian artery (PRAA‐SA‐LA) was detected. A complete‐type persistent left cranial vena cava (PLCVC) was also observed. This is the first report describing the association between PRAA‐SA‐LA and PLCVC in a dog with megaoesophagus.